1990
DOI: 10.1002/1097-0142(19900415)65:8<1737::aid-cncr2820650813>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiotherapy in the treatment of malignant sweat gland neoplasms

Abstract: Malignant sweat gland neoplasms are rare tumors. Historically, the principal mode of treatment has been local surgical excision. Eight published studies show that greater than 50% of patients develop either local tumor recurrence after surgery or regional lymph node metastases. Most patients have evidence of locoregional failure before distant metastases are detected. Three patients were recently referred to the University of Arizona Cancer Center for consideration of irradiation after resection of such tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
73
0
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 18 publications
1
73
0
5
Order By: Relevance
“…8 The dose of radiation was 70 gray for surgical bed and 50 gray for regional lymphatic chains. 8 However, in our case patient was not subjected to any adjuvant therapy in the form of chemotherapy or radiotherapy, since wound was allowed to heal by granulation tissue formation followed by skin grafting. Hence, patient was not subjected to radiotherapy.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…8 The dose of radiation was 70 gray for surgical bed and 50 gray for regional lymphatic chains. 8 However, in our case patient was not subjected to any adjuvant therapy in the form of chemotherapy or radiotherapy, since wound was allowed to heal by granulation tissue formation followed by skin grafting. Hence, patient was not subjected to radiotherapy.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…Harari and colleagues reported complete remissions with external beam radiotherapy of sweat gland tumours with positive margins after surgery. 14 Lerner et al have mentioned that their patient with unresectable metastatic hidradenocarcinoma had complete clinical and radiological response with 3 months of oral capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that certain histological features such as dermal lymphatic invasion, nerve sheath involvement, deep structural infiltration, positive resected margins, and extracapsular lymph node extension may identify a high risk of recurrence and merit postoperative radiotherapy. [12] The role of chemotherapy in eccrine sweat gland carcinomas, and especially malignant acrospiromas, is not clear. Various case reports and case series have reported on the use of a multitude of drugs in various sweat gland carcinomas including cyclophosphamide and doxorubicin, bleomycin, cisplatin, mitomycin C, with partial response and a median duration of response of 4 to 16 months.…”
Section: Discussionmentioning
confidence: 99%